2024
DOI: 10.3390/app14073009
|View full text |Cite
|
Sign up to set email alerts
|

The Fermentation of Orange and Black Currant Juices by the Probiotic Yeast Saccharomyces cerevisiae var. boulardii

Andrea Maria Patelski,
Urszula Dziekońska-Kubczak,
Maciej Ditrych

Abstract: Throughout history, the fermentation of fruit juices has served as a preservation method and has enhanced the retention of bioactive constituents crucial for human well-being. This study examined the possibility of orange and black currant juice fermentation with the probiotic yeast Saccharomyces cerevisiae var. boulardii. Saccharomyces bayanus was used as the reference. The ethanol concentration of the orange juices fermented without added glucose was close to 27 g/L. Adding glucose to the juice increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
0
1
Order By: Relevance
“…The initial pH value of the samples (F25_0; F25_10; F25_20; F25_100) with the addition of 0.25% (w/w) furcellaran ranged from 2.77 to 6.18 and for the samples (F50_0; F50_10; F50_20; F50_100) with 0.50% (w/w) furcellaran from 2.77 to 6.14. The initial pH of the blackcurrant juice used in the study was slightly lower than that reported by Kelanne et al [40] and Patelski et al [41]. Additionally, the initial pH values of the whey were lower compared to the study by Levkov et al [42].…”
Section: Psychicochemical and Turbidity Analysescontrasting
confidence: 58%
“…The initial pH value of the samples (F25_0; F25_10; F25_20; F25_100) with the addition of 0.25% (w/w) furcellaran ranged from 2.77 to 6.18 and for the samples (F50_0; F50_10; F50_20; F50_100) with 0.50% (w/w) furcellaran from 2.77 to 6.14. The initial pH of the blackcurrant juice used in the study was slightly lower than that reported by Kelanne et al [40] and Patelski et al [41]. Additionally, the initial pH values of the whey were lower compared to the study by Levkov et al [42].…”
Section: Psychicochemical and Turbidity Analysescontrasting
confidence: 58%